Pengaruh Faktor Spesifik Perusahaan dan Anggaran Infrastruktur Terhadap Harga Saham Perusahaan Sektor Infrastruktur, Utilitas dan Transportasi Kategori Syariah - Sa’bana, Rifqi Fauzan; Mai, Muhamad Umar; Pakpahan, Rosma; Hermawan, Dadang (Journal of Applied Islamic Economics and Finance, 2023)
The purpose of this study is to ascertain whether certain corporate variables, such as ROE, DER, NPM, EPS, and Infrastructure Budget, have an effect on the stock prices of companies in the infrastructure, utilities, and transportation sectors that are listed on the ISSI. The descriptive and quantitative research approach that makes use of multiple linear regression analysis. ROE, DER, NPM, EPS, Infrastructure Budget, and the stock prices of partient enterprises from 2017-2021 are among the research’s study objects. With a sample size of 28 companies, the research focuses on infrastructure, utility, and transportation corporations that are listed in the ISSI. According to the research findings, DER and EPS have a significant impact on stock prices. However, ROE, NPM, and infrastructure budget do not have an influence on stock prices. Simultaneously, the stock prices of companies in the infrastructure, utilities, and transportation sectors listed on ISSI from 2017-2021 are influenced by ROE, DER, NPM, EPS, and infrastructure budget.